Bimetallic ZnFe2O4 nanosheets prepared via electrodeposition as binder-free high-performance supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Park, Chanwoo; Kim, Yongil; Lee, Hae-Seok; Yoon, Sam S. (Applied Surface Science, 2021)
Binder-free bimetallic ZnFe2O4 nanosheets were fabricated using one-step electrodeposition, which facilitated excellent electrical contact between the ZnFe2O4 nanosheets and the nickel substrate. The resultant numerous ZnFe2O4 nanosheets with their cubic spinel structures promote interfacial activity to enhance the electrochemical and Faradaic redox reactions. The metallic Zn and Fe from the cubic spinel structure of ZnFe2O4 attract electrolytic ions and increase the energy-storage capability, thus yielding a specific capacitance of 1093 F.g(-1) at a current rate of 1 A.g(-1). Different samples were prepared by varying the amount of metal salts in the electrodeposition solution while maintaining a constant ZnNt:FeSO4 concentration ratio of 1:2 for all cases. The optimal electrode composition, which yielded an energy density of 54 Wh.kg(-1) and a capacitance retention of 93.5% at N = 5000 charge-discharge cycles, was identified.
Keywords: Bimetallic; Electrodeposition; Energy storage device; supercapacitor; ZnFe2O4 nanosheet